Artikel Review: Dampak Limbah Farmasi terhadap Lingkungan dan Upaya Pengelolaannya di Industri - Muhammad Rezky Wahyudi; Hidayatur Rizky; Ufaul Apriani; Nor Latifah (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
The pharmaceutical industry produces solid, liquid, and gaseous waste containing active pharmaceutical ingredients that pose serious environmental risks. These wastes can disrupt ecosystems and accelerate antimicrobial resistance. This systematic literature review examines pharmaceutical waste concepts, classifications, characteristics, and relevant regulatory frameworks. It also addresses ecotoxicological effects on aquatic and terrestrial ecosystems, antibiotic contamination and resistance, water and soil pollution, treatment technologies, industrial policies, and best practices. Findings show that conventional wastewater treatment is largely ineffective at removing pharmaceutical residues, resulting in their presence in surface water, soil, and even drinking water. Compounds such as β-blockers, cytostatics, antibiotics, and hormones harm aquatic life by impairing reproduction and causing mutations. Antibiotic-laden industrial waste contributes to the emergence of resistant bacteria. Recommended treatment methods include biothermal processes, advanced oxidation (e.g., UV/H₂O₂, ozonation), adsorption (activated carbon), coagulation-flocculation, and controlled incineration. Stronger enforcement of hazardous waste regulations (e.g., Government Regulation No. 101/2014, Ministry of Environment and Forestry Regulation No. 56/2015) and adherence to WHO (2025) guidelines are essential. In conclusion, multisectoral collaboration (One Health), improved waste treatment capacity, and adoption of best practices are crucial to preventing pharmaceutical pollution and promoting environmental sustainability.